The Influence of Perceptions of Ease, Usability and Risk on the Interest in Using e-commerce- based Accounting Information Systems for Accounting Students at UNP Kediri - Zulaikah, Dewi; Widiawati, Hestin Sri; Linawati, Linawati (Universitas Nusantara PGRI Kediri, 2023)
Research Objective: The purpose of this study was to determine the effect of interest in using an e-commerce based accounting information system and to be able to analyze perceptions of convenience, usability, risk. Research Method: This research is a quantitative study with an associative approach. The sampling technique uses a purposive sampling technique in the form of a non-probability method. The population in this study were students at Nusantara University PGRI Kediri who had taken the Accounting Information Systems course in the 2019-2020 class. The sample obtained was 121 respondents. The research data used the SPSS (Software Statistical Package for Science) analysis technique version 21. Research Finding: The results of this study indicate that perceptions of convenience, usability and risk have a positive and significant impact on interest in using e-commerce based accounting.